Bandwidth brokers of instantaneous and book-ahead requests for differentiated services networks - Lin, YD; Chang, CH; Hsu, YC (My University, 2002)
The Quality of Service (QoS) reservations in Differentiated Service (DiffServ) networks can be classified into two sets: Book-ahead (BA) requests and Instantaneous Requests (IRs). When an admitted BA request becomes active, some ongoing IRs is dropped when the bandwidth is insufficient for supporting both IRs and BA requests. The admission control should predict the lifetime, i.e. look-ahead time, of the IRs to prevent the admitted IRs from being dropped, The control should then check whether the available bandwidth during the look-ahead time is sufficient for the incoming IRs. We propose an application-aware look-ahead admission control for IRs, which determines the lookahead time for specific types of IR applications. An admitted BA request might block subsequent ones that could bring more effective revenue. Thus, we propose the deferrable model of the admission control for BA requests, Simulation results indicate that the application-aware look-ahead admission control successfully reduces the dropping probability and wasted revenue of IRs by up to 10 times and 30%, respectively. Besides, the deferrable model indeed results in more BA effective revenue.
Keywords: IR; book-ahead; DiffServ; QoS